PENGARUH HARGA, KUALITAS PRODUK, DAN KUALITAS PELAYANAN TERHADAP KEPUASAN KONSUMEN (SUATU KASUS PADA DAGING GRILL DI CILAMAYA CAFE AND RESTO CILEGON) - Sheptinaz Putri Herdiana; Ratna Mega Sari; Suherman Suherman; Andjar Astuti (JURNAL AGRIBISNIS TERPADU, 2023)
This study aims to determine the effect of price, product quality, and service quality on grilled meat consumer satisfaction at Cilamaya Cafe and Resto Cilegon. The number of respondents in this study were 40 respondents, namely grilled meat consumers at Cilamaya Cafe and Resto Cilegon. Sampling using purposive sampling. Data collection techniques through observation, interviews, questionnaires, and literature study. In proving and analysis, the data processing method used in this study uses validity test, reliability test, normality test, multicollinearity test, heteroscedasticity test, multiple linear regression analysis test, and analysis of the coefficient of determination (R2), T test (partial), and F test (simultaneous). The test results using the T test in this study can mean that: price has a positive and significant effect on consumer satisfaction (3,496 > 2,028). Product quality has a positive and significant effect on customer satisfaction (4.752 > 2.028). Service quality has a positive and significant effect on customer satisfaction (2.147 > 2.028). While the results of testing using the F test in this study can say that: price, product quality, and service quality have a positive and significant effect on customer satisfaction (120.193 > 2.86).